Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jat.3812
|View full text |Cite
|
Sign up to set email alerts
|

Development of an oral reference dose for the perfluorinated compound GenX

Abstract: Ammonium 2,3,3,3‐tetrafluoro‐2‐(heptafluoropropoxy)‐propanoate, also known as GenX, is a processing aid used in the manufacture of fluoropolymers. GenX is one of several chemistries developed as an alternative to long‐chain poly‐fluoroalkyl substances, which tend to have long clearance half‐lives and are environmentally persistent. Unlike poly‐fluoroalkyl substances, GenX has more rapid clearance, but has been detected in US and international water sources. There are currently no federal drinking water standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…6 The increase in hepatic cell proliferation observed in that study is consistent with evidence for GenX activation of PPARa signaling, as evidenced by increased peroxisomal enzyme activity, liver hypertrophy, and transcriptomic signaling. 6,11 Relatedly, other PFAS have been shown to activate PPARa. 12 To further explore potential mechanisms of toxicity and relevance of such underlying the liver lesions observed in mice, herein we report transcriptomic and immunohistochemical analyses in male and female mice from a 90-day Organisation for Economic Co-operation and Development (OECD) 408 guideline oral toxicity study.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…6 The increase in hepatic cell proliferation observed in that study is consistent with evidence for GenX activation of PPARa signaling, as evidenced by increased peroxisomal enzyme activity, liver hypertrophy, and transcriptomic signaling. 6,11 Relatedly, other PFAS have been shown to activate PPARa. 12 To further explore potential mechanisms of toxicity and relevance of such underlying the liver lesions observed in mice, herein we report transcriptomic and immunohistochemical analyses in male and female mice from a 90-day Organisation for Economic Co-operation and Development (OECD) 408 guideline oral toxicity study.…”
Section: Introductionsupporting
confidence: 83%
“…These findings align with a similar reevaluation of male mice exposed to GenX for approximately 90 days. 6,8 Therein, it was argued that apoptosis was part of a PPARa MOA and not indicative of liver toxicity per se. According to the Hall criteria 40 for assessing liver toxicity, sequelae related to PPARa have limited human relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies exist showing the dangers of PFOS and PFOA, currently there has been limited research on the health outcomes caused by other PFAS compounds. However, some mammalian studies on PFNA, GenX, and PFHxS have indicated similar negative health effects (Rockwell et al 2013 ;Ramhøj et al 2018 ;Thompson et al 2019 ). Thus, more research is needed on exposure levels in humans, the scale of exposure in the United States, and how exactly different PFAS affect human organs (CDC 2019 ).…”
Section: What Are the Dangers Of Pfas For Human Health And The Aquatimentioning
confidence: 97%
“…; Thompson et al. ). Thus, more research is needed on exposure levels in humans, the scale of exposure in the United States, and how exactly different PFAS affect human organs (CDC ).…”
Section: What Are Pfas and Where Are They Found?mentioning
confidence: 97%